Conduits of Chaos: Social Media and Intersections of Home, School, and Community Cultures - Lane, James; Robinson, Shaquanah; Bowen, Alyncia (Journal of Organizational Psychology, 2023)
Social media are a cultural leveler. Most students have cell phones, through which they may post and/or view cyberbullying threads, hate diatribes, and recordings of fights. Such posts create a toxic and symbiotic culture that seemingly transcends race and income. Closer examination suggests that social media and digital devices can be turbulent conduits that spew neighborhood chaos into schools, intersecting community and school events. Impoverished African American communities spawned by systemic racism are not immune from such dysfunction. An application of an Africana lens suggests that initial attempts to understand these phenomena from a White hegemonic perspective are inadequate and show that the issues require more detailed scrutiny. Awareness of events through an Africana cultural perspective reveal resilience and opportunities for transformation. Africana theory suggests that the infusion of social justice initiatives can transform groups into more equitable communities by creating powerful opportunities for cultural change, communication, and understanding.